Abner de Burgos and the Transfer of Philosophical Knowledge between Judaism and Christianity. - Sadik, Shalom (Medieval Encounters, 2016)
Abner de Burgos (Alfonso de Valladolid, ca. 1265-1347) was perhaps the most important philosopher in the stream of Jewish-Spanish apostates in the fourteenth and fifteenth centuries. In the first part of his intellectual career, Abner was an Aristotelian Jewish philosopher. However, around the age of sixty, he became a Neo-Platonic Christian and devoted the rest of his life to trying to convert Jews to Christianity. As a philosopher who spent more than fifty years of his life as a Jew, and more than twenty-five years as a Christian, we may expect to find that Abner played a major role in the transfer of philosophical knowledge between the two religions. Here, we will see that the reality is in fact different. Abner's familiarity with philosophical material was almost entirely limited to parts of the Spanish-Jewish curriculum. His philosophical influence was almost entirely limited to Spanish Jews, and it is only through these Jews that he had any kind of influence upon Christians in general and Western philosophers in particular.